Preparation method of slow-release urea and application of slow-release urea in saline alkali soil remediation
By performing mechanical chemical method on the uneven rodstone, load ammonium uric acid on its surface and mixes granules with urea to prepare slow -release urea, solve the problem of nitrogen loss during the use of urea fertilizers, and realize it more. Efficient nitrogen use and more uniform nitrogen supply.
Patent Information
- Application Number
- CN202411440255.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-15
- Publication Date
- 2025-01-24
AI Technical Summary
During use, existing urea fertilizers are prone to nitrogen loss due to dissolution and volatility, which affects the nitrogen utilization efficiency of crops and nitrogen supply during the growth period.
The surface of ammonium uric acid uric acid uterine is loaded to the surface of the amino sill signal coupling agent, and the surface of the ammonium urea can be used to form a bumpbone and mixed with urea to prepare mild release urea.
This method By reducing the dissolving speed and decomposition speed of urea, reducing the loss and volatilization of nitrogen, improving the efficiency of nitrogen, meeting the nitrogen demand of the entire growth period of the crop, and avoiding the phenomenon of fry.
Smart Images

Figure FT_1
Abstract
Description
Technical Field
[0001] The invention belongs to the field of slow-release fertilizers, and in particular relates to a method for preparing slow-release urea. Background Art
[0002] Urea, also known as urea and carbonamide, has a chemical formula of CO(NH 2 ) 2 , containing 46% nitrogen (N), which is the highest nitrogen content among solid nitrogen fertilizers and is a neutral quick-acting fertilizer. Compared with ordinary urea, slow-release urea can reduce nitrogen leaching and volatilization by reducing the dissolution rate of urea or the rate at which urea decomposes into ammonia, thereby improving nitrogen utilization efficiency, meeting the nitrogen nutrients required by crops throughout the growth period, and preventing crop seedling burn. Summary of the invention
[0003] The object of the present invention is to provide a slow-release urea based on attapulgite.
[0004] To achieve the above purpose, the present invention adopts the following technical solutions: A method for preparing slow-release urea comprises the following steps: (1) Ammonium urate was loaded onto the surface of aminosilane coupling agent-modified attapulgite by mechanochemical method to obtain ammonium urate functionalized attapulgite; (2) Urea and ammonium urate functionalized attapulgite are mixed and granulated to obtain slow-release urea.
[0005] Preferably, in step (1), the amount of ammonium urate used is 2-5% of the mass of the aminosilane coupling agent-modified attapulgite.
[0006] Preferably, the equipment used in the mechanochemical method is a high-speed ball mill. More preferably, the grinding time is 1 to 3 hours.
[0007] Preferably, in step (2), the amount of urea used is 20-30% of the mass of the ammonium urate functionalized attapulgite.
[0008] Preferably, in step (2), urea and ammonium urate functionalized attapulgite are first mixed and granulated, and then the obtained granules and aminosilane coupling agent modified attapulgite are mixed and granulated to obtain slow-release urea.
[0009] More preferably, the amount of urea used is 20-30% of the mass of ammonium urate functionalized attapulgite, and the amount of aminosilane coupling agent modified attapulgite used is 1-3% of the total mass of urea and ammonium urate functionalized attapulgite.
[0010] Preferably, in step (2), urea and ammonium urate functionalized attapulgite and aminohippuric acid functionalized attapulgite are mixed and granulated to obtain slow-release urea; Alternatively, urea and ammonium urate functionalized attapulgite are first mixed and granulated, and then the obtained granules and aminohippuric acid functionalized attapulgite are mixed and granulated to obtain slow-release urea.
[0011] Preferably, the aminohippuric acid functionalized attapulgite is obtained by spraying an aminohippuric acid solution onto the surface of the attapulgite modified with an aminosilane coupling agent; More preferably, the amount of urea used is 20-30% of the mass of ammonium urate functionalized attapulgite, and the amount of aminohippuric acid functionalized attapulgite used is 1-3% of the total mass of urea and ammonium urate functionalized attapulgite.
[0012] More preferably, the amount of aminohippuric acid used is 10-15% of the mass of the aminosilane coupling agent-modified attapulgite, and the aminohippuric acid solution is sprayed onto the surface of the aminosilane coupling agent-modified attapulgite.
[0013] Preferably, the water-absorbing resin is coated on the surface of the slow-release urea obtained in step (2) by an in-situ polymerization coating method.
[0014] More preferably, the water-absorbing resin is corn starch grafted acrylic water-absorbing resin. Compared with conventional acrylic water-absorbing resin, corn starch grafted acrylic water-absorbing resin has good salt resistance.
[0015] Preferably, the operation of coating the slow-release urea with corn starch grafted acrylic acid water-absorbing resin comprises: The corn starch solution is heated, and after gelatinization, acrylic acid monomer and slow-release urea are added, stirred evenly, and then a cross-linking agent and an initiator are added to carry out a polymerization reaction.
[0016] More preferably, the amount of acrylic acid monomer used is 15-40% of the mass of corn starch, and the degree of neutralization of acrylic acid monomer is 70-80%.
[0017] More preferably, the mass ratio of the slow-release urea to the corn starch is 1-3:1.
[0018] More preferably, the cross-linking agent is N,N'-methylenebisacrylamide, and the amount used is 20-60% of the mass of corn starch.
[0019] More preferably, the initiator is ammonium sulfite, and the amount used is 30-40% of the mass of the acrylic acid monomer.
[0020] More preferably, the polymerization temperature is 80-90°C.
[0021] Preferably, a certain amount of suspending agent is added to the reaction system. More preferably, the suspending agent is added before the slow-release urea.
[0022] More preferably, the suspending agent is sodium alginate and sodium carboxymethyl cellulose, and most preferably, the mass ratio of sodium alginate to sodium carboxymethyl cellulose is 1:3.
[0023] More preferably, in the reaction system, the concentration of the suspending agent is 20-30 g / mL.
[0024] The aminosilane coupling agent modified attapulgite can be prepared by a method comprising the following steps: The attapulgite is first soaked in acid solution, washed and then mixed with an aminosilane coupling agent in a solvent for reaction, thereby obtaining the aminosilane coupling agent modified attapulgite.
[0025] Preferably, the acid solution may be hydrochloric acid with a concentration of 0.1 to 12 mol / L.
[0026] Preferably, the soaking temperature is 80-90°C and the soaking time is 1-2 hours.
[0027] Preferably, the mass ratio of the aminosilane coupling agent to the acid-treated attapulgite is 1 to 3:1, more preferably 1.5 to 2.5:1.
[0028] Preferably, the solvent is ethanol aqueous solution, the reaction temperature is 80-90° C., and the reaction time is 3-5 h. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 This is a schematic diagram of the structure of the homemade soil column leaching device. DETAILED DESCRIPTION
[0030] The technical solution of the present invention is further described in detail below in conjunction with embodiments.
[0031] In the present invention, the aminosilane coupling agent modified attapulgite (HO-ATP) can be prepared by using a commercially available product or an existing conventional method, and the preparation process is as follows: Take 10 g of attapulgite ore (ATP) powder and add it to 200 mL of 6 mol / L hydrochloric acid solution. After stirring at 80 °C for 1 h, filter the solution, wash it thoroughly with distilled water until the filtrate is neutral, and dry it thoroughly at 80 °C. Take 5 g of the dried powder and add it to 100 mL of ethanol-water solution, and continue to stir to make it evenly dispersed. When the temperature rises to 80 °C, add 10 mL of silane coupling agent (KH-550). After reacting for 4 h, wash it thoroughly with ethanol, then filter it with distilled water to make the filtrate neutral, and obtain HO-ATP.
[0032] Example 1 (1) After ammonium urate (AU) and HO-ATP were mixed evenly, they were added into a high-speed ball mill and ground for 1 h to obtain ammonium urate functionalized attapulgite (AU-ATP), wherein the amount of ammonium urate added was 2% of the mass of HO-ATP.
[0033] (2) Urea and AU-ATP were mixed evenly in a mass ratio of 1:4, and added into a round pot granulator to form granules of 1-3 mm to obtain slow-release urea.
[0034] Example 2 (1) After ammonium urate and HO-ATP are mixed evenly, they are added into a high-speed ball mill (20,000 rpm) and ground for 2 h to obtain AU-ATP, wherein the amount of ammonium urate added is 3% of the mass of HO-ATP.
[0035] (2) After aminohippuric acid (PAH) is dissolved in dilute hydrochloric acid, it is sprayed onto the surface of HO-ATP to obtain aminohippuric acid functionalized attapulgite (PAH-ATP), wherein the amount of aminohippuric acid used is 12% of the mass of HO-ATP.
[0036] (3) Mix urea and AU-ATP in a mass ratio of 1:4 and add them into a round pot granulator to make granules A of 1-3 mm.
[0037] (4) Particle A is mixed with PAH-ATP, and after mixing, the mixture is added into a round pot granulator for granulation, so that PAH-ATP is coated on the surface of particle A to obtain slow-release urea, wherein the amount of PAH-ATP used is 2% of the mass of particle A.
[0038] Example 3 The preparation of slow-release urea was the same as in Example 2, except that the amount of ammonium urate added was 5% of the mass of HO-ATP.
[0039] Example 4 The preparation of slow-release urea is the same as in Example 2, except that the amount of aminohippuric acid used is 10% of the mass of HO-ATP.
[0040] Example 5 The preparation of slow-release urea is the same as in Example 2, except that the amount of aminohippuric acid used is 15% of the mass of HO-ATP.
[0041] Example 6 The preparation of slow-release urea is the same as that in Example 2, except that the mass ratio of urea to AU-ATP is 1:5.
[0042] Example 7 The preparation of slow-release urea was the same as in Example 2, except that the mass ratio of urea to AU-ATP was 1:3.5.
[0043] Example 8 The preparation of slow-release urea is the same as in Example 2, except that the amount of PAH-ATP used is 1% of the mass of particle A.
[0044] Example 9 The preparation of slow-release urea is the same as in Example 2, except that the amount of PAH-ATP used is 3% of the mass of particle A.
[0045] Example 10 (1) After ammonium urate and HO-ATP are mixed evenly, they are added into a high-speed ball mill and ground for 2 hours to obtain AU-ATP, wherein the amount of ammonium urate added is 3% of the mass of HO-ATP.
[0046] (2) Mix urea and AU-ATP in a mass ratio of 1:4 and add them into a round pot granulator to make granules A of 1-3 mm.
[0047] (4) Mix granules A and HO-ATP, add the mixture into a round pot granulator for granulation, so that HO-ATP is coated on the surface of granules A to obtain slow-release urea. The amount of HO-ATP used is 2% of the mass of granules A.
[0048] Embodiment 11 (1) After ammonium urate and HO-ATP are mixed evenly, they are added into a high-speed ball mill and ground for 2 hours to obtain AU-ATP, wherein the amount of ammonium urate added is 3% of the mass of HO-ATP.
[0049] (2) After aminohippuric acid is dissolved in dilute hydrochloric acid, it is sprayed onto the surface of HO-ATP to obtain PAH-ATP, wherein the amount of aminohippuric acid used is 12% of the mass of HO-ATP.
[0050] (3) Urea, AU-ATP and PAH-ATP were mixed and added into a round pot granulator to make granules of 1 to 3 mm to obtain slow-release urea, wherein the mass ratio of urea to AU-ATP was 1:4, and the amount of PAH-ATP was 2% of the total mass of urea and AU-ATP.
[0051] Example 12 Acrylic acid (1.8 g) was neutralized with ammonium bicarbonate (1.48 g) to obtain an acrylic acid monomer solution for later use.
[0052] 85 mL of distilled water and 7.5 g of corn starch were added to the container, and the mixture was gelatinized in a constant temperature water bath at 85 ° C and 200-500 r / min for 30 min. After a uniform and stable white emulsion was formed, 25 mL of sodium alginate solution (concentration of 2wt%) and 1.5 g of sodium carboxymethyl cellulose were added, and then the acrylic acid monomer solution was added. The mixture was stirred at 80-90 ° C for 30 min, and 15 g of the slow-release urea prepared in Example 2 was added. After stirring for 10 min, 3 g of the cross-linking agent N,N'-methylenebisacrylamide and 0.6 g of the initiator ammonium sulfite were added in sequence. The mixture was reacted at 80-90 ° C for 2 h, and the unreacted monomers on the surface were washed with deionized water. The mixture was dried in a vacuum drying oven at 80 ° C for 24 h to obtain a slow-release urea coated with a water-absorbing resin on the surface.
[0053] Embodiment 13 The slow-release urea of Example 10 is coated with a water-absorbing resin, and the coating process is the same as that of Example 12.
[0054] Embodiment 14 The slow-release urea of Example 11 is coated with a water-absorbing resin, and the coating process is the same as that of Example 12.
[0055] Embodiment 15 The slow-release urea of Example 2 was coated with a water-absorbing resin. The coating process was the same as that of Example 12, except that the amount of corn starch used was 5 g.
[0056] Example 16 The slow-release urea of Example 2 was coated with a water-absorbing resin. The coating process was the same as that of Example 12, except that the amount of corn starch used was 10 g.
[0057] Comparative Example 1 (1) After aminohippuric acid is dissolved in dilute hydrochloric acid, it is sprayed onto the surface of HO-ATP to obtain PAH-ATP, wherein the amount of aminohippuric acid used is 12% of the mass of HO-ATP.
[0058] (2) Mix urea and HO-ATP in a mass ratio of 1:4 and add them into a round pot granulator to make granules A of 1-3 mm.
[0059] (4) Particle A is mixed with PAH-ATP, and after mixing, the mixture is added into a round pot granulator for granulation, so that PAH-ATP is coated on the surface of particle A to obtain slow-release urea, wherein the amount of PAH-ATP used is 2% of the mass of particle A.
[0060] (5) The slow-release urea obtained in step (4) is coated with a water-absorbing resin, and the coating process is the same as that in Example 12.
[0061] Comparative Example 2 (1) Mix urea and HO-ATP in a mass ratio of 1:4 and add them into a round pot granulator to make granules A of 1-3 mm.
[0062] (2) Granule A is then mixed with HO-ATP, and after mixing, the mixture is added to a round pot granulator for granulation, so that HO-ATP is coated on the surface of granule A to obtain slow-release urea, wherein the amount of HO-ATP used is 2% of the mass of granule A.
[0063] (3) The particles obtained in step (2) are coated with a water-absorbing resin, and the coating process is the same as that in Example 12.
[0064] Sustained release performance test: Figure 1 The following is a schematic diagram of the structure of the homemade soil column leaching device. The homemade soil column leaching device is a PMMA tube with an inner diameter of 8.2 cm, and the bottom is sealed with a 200-mesh gauze. 200 g of clean natural river sand (passed through a sieve with a pore size of 2-3 mm) was placed at the bottom of the tube, with a height of about 3 cm; then the corresponding weight of air-dried soil (passed through a sieve with a pore size of 2 mm) was placed according to the burial depth, and the soil layer height was 18 cm. Then 5 g of slow-release urea fertilizer was evenly spread on the surface of the soil layer; finally, 50 g of natural river sand was covered (to prevent the surface of the soil layer from being damaged during watering). On the first day of the experiment, 156 mL of distilled water was added to make it saturated. After that, the corresponding amount of distilled water was added every 2 days (starting from the second day of water addition) for leaching and the leaching solution was collected for the determination of urea loss. The results are shown in Table 1.
[0065] Table 1 Urea loss rate (cumulative) in different time periods sample Day 2 Day 20 Day 40 Day 60 Example 12 1.5% 20.6% 38.4% 51.2% Comparative Example 1 17.3% 31.6% 51.9% 82.1% Embodiment 13 14.1% 24.7% 42.3% 72.9% Embodiment 14 8.9% 25.9% 42.7% 63.9% Comparative Example 2 78.9% 100% / / Improvement performance test of saline-alkali soil: Use 500 kg per mu of land, deep plow 15 cm and mix thoroughly with saline-alkali soil. Age after normal watering and sample test after one month. The results are shown in Table 2.
[0066] Table 2 Test of the improvement effect of different products on saline-alkali land <![CDATA[Bulk density g / cm 3 > Porosity% pH pNa Water retention min Blank saline-alkali soil 1.54 42.9 9.5 0.79 34 Example 12 1.07 67.1 7.4 3.00 86 Comparative Example 1 1.36 49.6 7.8 2.89 52 Embodiment 13 1.29 52.3 8.5 2.56 48 Embodiment 14 1.34 59.1 8.9 1.27 61 Comparative Example 2 1.43 54.8 7.6 1.39 40 Finally, it should be noted that the above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art can still modify the technical solutions described in the aforementioned embodiments or replace some of the technical features therein by equivalents. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing a slow-release urea, comprising the following steps: (1) Ammonium urate was loaded onto the surface of aminosilane coupling agent-modified attapulgite by mechanochemical method to obtain ammonium urate functionalized attapulgite; (2) Urea and ammonium urate functionalized attapulgite are mixed and granulated to obtain slow-release urea.
2. The preparation method according to claim 1, characterized in that: In step (1), the amount of ammonium urate used is 2-5% of the mass of the aminosilane coupling agent-modified attapulgite.
3. The preparation method according to claim 1, characterized in that: In step (2), the amount of urea used is 20-30% of the mass of the ammonium urate functionalized attapulgite.
4. The preparation method according to claim 1, characterized in that: In step (2), urea and ammonium urate functionalized attapulgite are first mixed and granulated, and then the obtained granules and aminosilane coupling agent modified attapulgite are mixed and granulated to obtain slow-release urea; Preferably, the amount of urea used is 20-30% of the mass of ammonium urate functionalized attapulgite, and the amount of aminosilane coupling agent modified attapulgite used is 1-3% of the total mass of urea and ammonium urate functionalized attapulgite.
5. The preparation method according to claim 1, characterized in that: In step (2), urea, ammonium urate functionalized attapulgite, and aminohippuric acid functionalized attapulgite are mixed and granulated to obtain slow-release urea; Alternatively, urea and ammonium urate functionalized attapulgite are first mixed and granulated, and then the obtained granules are mixed and granulated with aminohippuric acid functionalized attapulgite to obtain slow-release urea; The aminohippuric acid functionalized attapulgite is obtained by spraying an aminohippuric acid solution onto the surface of the attapulgite modified by an aminosilane coupling agent; Preferably, the amount of urea used is 20-30% of the mass of ammonium urate functionalized attapulgite, and the amount of aminohippuric acid functionalized attapulgite used is 1-3% of the total mass of urea and ammonium urate functionalized attapulgite; Preferably, the amount of aminohippuric acid used is 10-15% of the mass of the aminosilane coupling agent-modified attapulgite, and the aminohippuric acid solution is sprayed onto the surface of the aminosilane coupling agent-modified attapulgite.
6. The preparation method according to any one of claims 1 to 5, characterized in that: The water-absorbing resin is coated on the surface of the slow-release urea obtained in step (2) by an in-situ polymerization coating method. Preferably, the water-absorbing resin is corn starch grafted acrylic acid water-absorbing resin.
7. The preparation method according to claim 6, characterized in that: The operation of corn starch grafted acrylic acid absorbent resin coating slow-release urea includes: Heat the corn starch solution, add acrylic acid monomer and slow-release urea after gelatinization, stir evenly, then add crosslinking agent and initiator to carry out polymerization reaction. Preferably, the amount of acrylic acid monomer is 15-40% of the mass of corn starch, and the neutralization degree of acrylic acid monomer is 70-80%; Preferably, the mass ratio of slow-release urea to corn starch is 1-3:1; Preferably, the cross-linking agent is N,N'-methylenebisacrylamide, and the amount used is 20-60% of the mass of corn starch; Preferably, the initiator is ammonium sulfite, and the amount used is 30-40% of the mass of the acrylic acid monomer; Preferably, the polymerization temperature is 80-90°C.
8. The preparation method according to claim 7, characterized in that: A certain amount of suspending agent is added to the reaction system. Preferably, the suspending agent is sodium alginate and sodium carboxymethyl cellulose, more preferably, the mass ratio of sodium alginate to sodium carboxymethyl cellulose is 1:3; Preferably, in the reaction system, the concentration of the suspending agent is 20-30 g / mL.
9. A slow-release urea obtained by the preparation method according to any one of claims 1 to 8.
10. Use of the slow-release urea according to claim 9 in saline-alkali soil remediation.